The Role of Banking in Reducing Poverty in 30 Indonesian Provinces - Afifa Wahyu TRIDEWI; Munawar ISMAIL; Susilo SUSILO (Indonesia Strategic Sustainability, 2023)
The line of thought in this research is about the role of banking in its role in reducing poverty in Indonesia. In accordance with Article 4 No. 10 of 1998 concerning banking, that banking supports the implementation of national development in order to increase equity, economic growth, and national stability towards improving people's welfare. The data used in this study is secondary data in the form of panel data from 2000 to 2018, namely savings, credit, GDP, poverty, inflation, and unemployment data. The analytical model used in this study is a multiple regression model of panel data